(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article explores the problems of the origin of the mythological plots of “red dogs” in the Kyrgyz genealogy, the environment in which mythological legends arose, as well as the philosophical and religious meanings of this scientific topic. The dog, like the wolf, has been a totem animal among the Kyrgyz and other Turkic-Mongolian peoples since ancient times, as proven by scientific research. In the beliefs of the Kyrgyz people, the dog performed security and protective functions against various diseases, disasters, etc. Killing a dog was considered a grave sin.